Thinking Through the Imagination : Aesthetics in Human Cognition - Kaag, John J., 1979- (Book collections on Project MUSE., 2014)
John Kaag explores these questions: What is the imagination? And where does the imagination come from? In order to answer them, Kaag explains the way that the concept of the imagination has been articulated in the history of Western philosophy, concentrating on its development in 18th century German idealism (primarily in the writings of Kant and Schiller) and in 19th century American pragmatism (embodied in the writings of C.S. Peirce). The goal of this intellectual history is to reveal a crucial point concerning the definition and the origins of the imagination and human creativity.